Pengaruh Metode Bervariasi dan Pemanfaatan Lingkungan Sekolah terhadap Peningkatan Hasil belajar IPA - Anang Supriantoro (STKIP PGRI SITUBONDO, 2022)
This study aims to determine the effect of various methods on learning achievement, determine the significant effect of the use of the school environment on learning achievement, and determine the effect of various methods and use of learning media. school environment on learning achievement. This research uses descriptive analysis method. The relationship between causal variables and types of quantitative data was analyzed by multiple linear regression. the influence of the method varies and the use of the school environment as the independent variable, while the dependent variable is student achievement. Samples were taken with saturated samples. For fifth grade students of SDN Cluster 2 School, Sambeng District, Lamongan Regency, descriptive analysis shows that the influence of various methods has a significant effect on learning achievement. The use of the school environment has a significant effect on learning achievement. The relationship between the influence of various methods and the use of the school environment on learning achievement is shown from the results of the analysis that the influence of various methods and the use of the school environment has a significant effect on learning achievement.